Drug-eluting balloon catheters in the treatment of left main coronary artery bifurcation lesions: 4-years follow-up. (14th October 2021) - Maximkin, D; Shugushev, Z; Chepurnoy, A; Gitelzon, E; Faybushevich, A
Abstract: Aim: To evaluate the long-term results of the use of drug-eluting balloon catheters in patients with Left Main (LM) bifurcation stenosis. Methods: The analysis involved 142 patients with true bifurcations of the Left Main. Randomization in 2 main groups: Group I (n=52) included patients, who received kissing- dilatation with traditional NC balloon catheters and Group II (n=52), who had a kissing-dilatation of the main bifurcation artery with a traditional NC balloon catheters, and a side branch - with drug-eluting balloon catheters. In retrospectively, the third (III) control group (n=38) was formed, where the two-stent technique was performed. All patients from main groups had previously performed "Provisional T" stenting and final "kissing balloons" dilation technique. Coronary angiography and OCT were performed to evaluate the results of all patients. Inclusion criteria: true LM bifurcation stenoses according to QCA and OCT; SYNTAX score <32. Primary endpoints: incidence of MACE - death, MI, re-interventions. Secondary endpoints: the incidence of restenosis and late stent thrombosis. Results: The long-term results after 4-years were observe in 46 patients from Group I and 48 patients from Group II. Restenosis of the side branch of more than 50% according to QCA was detected in 12 patients (26.0%) from Group I and in 5 patients (10.4%) from Group II (p<0.05). In-stent restenosis of the main vessel of more than 50% according to QCA was detected in 4 patients (8.6%) from Group I and in 1 patients (2.1%) from Group II (p<0.05). In patients from group I, the average MLA in the side branch after 4-years compared with data after PCI was 5.58±1.34 and 4.12±1.21 mm 2, respectively (p<0.05), in the main branch – 6.34±1.56 and 5.88±1.14 mm 2, respectively (p>0.05). In patients from Group II, the average MLA were, respectively, 5.38±1.24 and 5.01±1.14 mm 2 in side branch (p>0.05) and 6.68±1.75 and 6.36±1.22 mm 2 in main branch (p>0.05). When comparing the data of MLA in the side branch in groups I and II, there was a significant difference (4.12±1.21 vs. 5.01±1.14 mm 2 ; p<0.05).The repeat revascularization, in connection with the detected ischemia was performed in 7 patients (15.2%) from Group I and in 1 patients (2.1%) from Group II (p<0.05). In the Group I was observed non-fatal myocardial infarction in 2 patients (4.3%). The total incidence of MACE were 19.5 vs. 2.1% in groups I and II respectively (χ 2 =7.321; p<0.001). The survival without MACE was 97.9 and 80.5%, respectively (p=0.0219). Conclusions: The use of dug-eluting balloon catheters for the "Provisional T" stenting in patients with true LM bifurcation stenosis, associated with good prognosis and demonstrated significantly lower frequency of MACE and side branch restenosis, according to OCT data, compared with patients who used traditional NC balloon catheters for "kissing-dilatation" and two-stent technique strategy. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Russian academic excellence project 5-100